The Extent of the Application of the Libyan Technical Education Faculties for Strategic Planning and its Impact on the Activation Axes of the Total Quality: An Empirical Study on the Technical Education Faculties in the City of Tripoli - Mustafa Abdullah (University of Science and Technology, Yemen, 2015)
This paper has aimed to identify the extent of the application of strategic planning with the teaching staff members in the faculties of technical education, it has also aimed to identify the extent of applying the total quality axes in the technical education faculties as it has perceived by the teaching staff members. The focus was on the axes such as (characterization of the curriculum, rules and regulations, educational media and information technology, teaching staff members). In addition, this paper has also aimed to identify the impact of the application of the concept of strategic planning on the total quality axes. The population of this study has included all teaching staff members, and a random sample was chosen. A  number of (90) questionnaires have distributed, and a number of (58) was recovered of the total questionnaires distributed , and has utilized  the Statistical Package for Social Sciences ( SPSS ) in order to analyze the questionnaires . Among the elements of the statistical analysis used in this study duplicates and arithmetical averages, standard deviations, and coefficient alpha Cronbach to check the stability of the axes of the study, in addition to testing simple and multi regression analysis to examine the impact. Using the (t) test for one sample to test and see the impact of this application on the total quality axes. Through the analysis of the data, the study has reached the following findings: 1-    The technical education faculties are applying the concept of strategic planning , as well as the axes of total quality management which have subjected to testing and verification including ( characterization curriculum , rules and regulations , educational media and information technology, faculty members ), where the result of the application was moderately. 2-    The study showed the presence of a statistically significant impact of strategic planning on the total quality axes under study. 3-    The study also presented no statistically significant effect of the concept of strategic planning on the application of educational media and Information Technology.